Probing neutrino mass ordering with supernova neutrinos at NOνA including the effect of sterile neutrinos - Papia Panda; Rukmani Mohanta (Nuclear Physics B)
In this work, we explore the possibility of probing the mass ordering sensitivity as a function of supernova distance in the context of the ongoing neutrino experiment NOνA. We provide a detailed study of the active-active and active-sterile mixing frameworks, illustrating how supernova neutrinos can be used to realize the existence of sterile neutrinos. Interestingly, we infer that observation of the NC channel alone can differentiate between the presence and absence of sterile neutrinos. Our results indicate that the primary channel of NOνA can distinguish normal mass ordering from inverted mass ordering at 5σ confidence level for a supernova explosion occurring at a distance of 5 kpc. Additionally, we examine the impact of systematic uncertainties on mass ordering sensitivity, showing that higher levels of systematics lead to a reduction in sensitivity. Similarly, the inclusion of energy smearing significantly diminishes ordering sensitivity.